Sport Spectatorship and Health Benefits: A Case of a Japanese Professional Golf Tournament - Watanabe, Yasuhiro; Qian, Tyreal Y.; Wang, Jerred J.; Pifer, N. David; Zhang, James J. (Frontiers in Psychology, 2020)
It has been well-argued that professional sport or mega sport events could serve as a catalyst for sport participation behaviors through direct and indirect trickle-down effects. However, there is limited research exploring the impact of spectator services during sport events on personal and collective well-being. Elaborating on the social-ecological model and the concept of market demand, this study attempted to fill the gap in the literature by measuring core product (player attraction, event attractiveness, and course characteristics) and peripheral spectator services (event services, event information, event amenity, and parking and transportation) of a professional golf tournament hosted in Japan and examining how these services factors would influence spectators’ length of stay at a golf event, physical activity as measured by step counts, self-rated health, and life satisfaction. Following the administration of a questionnaire to spectators at a Japanese professional golf tournament (N = 306) and conducting confirmatory factor analyses and structural equation modeling analyses, research findings revealed that the tournament-related spectator services would have an influence on physical activity, which could in turn influence self-rated health, and subsequently impact life satisfaction. That is, emphasizing the sense of accomplishment fulfilled in sport spectatorship is recommended for the well-being of the spectators. The findings of this study shed lights on the significance of promoting golf spectatorship as an effective means to facilitate a healthy lifestyle and in the meantime provide golf event marketers with a unique, positive benefit through which their events can be promoted.